Atendimento educacional especializado itinerante da rede municipal de São Paulo - Muradas, Tatiane Sanches Silva (2024)
The city of São Paulo incorporated into its Special Education Policy from the Perspective of Inclusive Education for the Municipal Education Network of São Paulo - RME/SP, the provision of Specialized Educational Services (AEE) in three modalities, namely: Collaborative AEE, Itinerant AEE and After-School AEE. In this context of various AEE, it is interesting to know: How does the Itinerant AEE modality occur, specifically regulated in the São Paulo Policy of Special Education from the Inclusive Perspective of the City of São Paulo? What relationships are established between the action of the itinerant AEE service and the regular classroom teacher that can contribute to the curricular access of the target audience of Special Education? How is the Itinerant AEE Service organized in the Education of the City of São Paulo/SP? Therefore, the importance of understanding the relationships established between PAAIs and their functional attributions is justified, outlining the general objective of the research to analyze the Specialized Educational Assistance Service in an Itinerant manner of the Municipal Education Network of São Paulo, as well as more specifically aiming to: a) characterize the professionals who make up the Support Services for school inclusion in the RME/SP, b) describe the roles assigned and performed by these professionals and list the Itinerant AEE and c) understand how the pedagogical practices related to the mediations assigned to the PAAI, who work in the Itinerant AEE, are being operationalized. To this end, to describe and analyze how the itinerant AEE occurs, an investigation was carried out involving the participation of thirty-seven Support and Monitoring Teachers for Inclusion, linked to the thirteen Regional Education Directorates - DREs, undertaking data collection from document analysis, questionnaires with open and closed questions and interviews in focus groups. The conclusions drawn from the PAAIs were that it is critically important to collaborate in the Itinerant AEE together with educational units. The urgent need to expand the PAAIs framework to serve Special Education Target Audience Students (EPAEE) was also highlighted, as well as the importance of considering the integrality of the subjects and the promotion of school inclusion as a means of stimulating universal and equitable participation. Finally, by analyzing nine educational policies, it was evident that the Itinerant AEE is only present in the São Paulo Policy for Special Education from the Perspective of Inclusive Education (PPEE-EI), in the context of the city of São Paulo. It was observed that there is, therefore, a rich opportunity to expand this modality to other smaller cities, expanding the offer of AEE services beyond what is traditionally carried out, that is, beyond the activities in multifunctional resource rooms in the afternoon, which has been prioritized in national educational policies for school inclusion.